Kenakalan Remaja dan Psikososial - Sigit Tri Utomo; Luluk Ifadah (Institut Agama Islam Syarifuddin Lumajang, 2019)
Adolescents are identical to mental development in both physical, social and spiritual dimensions. Adolescents are also indicated as a time of self discovery seeking to find identity through adaptation to the environment in which the learning environment, playground environment, and community environment interact. Some teenagers who are inappropriate in interacting with a good environment will have a negative impact on their mental development. They do anarchic, brutal, even trapped in immoral, drugs and go to jail. Here the author describes the importance of handling in the spiritual mental development of adolescents so that they do not fall prey to the westernerization pattern. Key words: Adolescents, Juvenile Delinquency, Psychosocial, Self Discovery Seeking